Mathematical analysis of Lassa fever epidemic with real data - Adnan Aslam; Takasar Hussain; Muhammad Ozair; Arfah Hafeez; Wedad Albalawi; Mohammed Zakarya; Nadir Omer (Alexandria Engineering Journal)
In this work, we discuss a lethal disease known as Lassa Fever through mathematical modeling. Seven dimensional mathematical model is considered as the system of ordinary differential equations. First, we compute the equilibrium point in which no disease exists then, after finding the reproduction number, both types of stabilities, local and global, of this equilibrium point is discussed. Endemic equilibrium is calculated and it is noted that stability of infection free equilibrium point is replaced by local stability of endemic equilibrium when basic reproduction number exceeds unity, so bifurcation occurs. The parameters involved in the problem are estimated through the model calibration with actual number of Lassa Fever patients appeared in Nigeria from January 2021 to 11th week of 2022. The crucial factors are pointed out which involves substantially in spreading the disease. Furthermore, control policies are designed and it is shown that how much the applied control measures may be effective in reducing the disease from the community.